Comparative study on nanofiber containing polypropylene-based composite mesh for abdominal wall hernia repair. (15th December 2021) - Mao, Ying; Meng, Yunxiao; Li, Shaojie; Li, Yan; Guidoin, Robert; Qiao, Yansha; Zhang, Ze; Brochu, Gaetan; Tang, Jianxiong; Wang, Lu
Graphical abstract: Highlights: Nanofibers containing composite meshes with different polypropylene substrates were fabricated. In vitro and in vivo studies on polypropylene meshes before and after incorporation with nanofibers were conducted. Polypropylene prostheses play a dominant role in mechanical support, while affecting cell proliferation and growth. Lightweight polypropylene-based composite mesh showed superior anti-adhesion effects and tissue compatibility. Abstract: Electrospun nanofibrous membranes (NFM) can serve as a physical barrier, employed to confer polypropylene (PP) mesh with anti-adhesion capability for repairing abdominal wall hernias. Still, the feasibility of NFM combined with different PP meshes was poorly researched. In this study, nanofiber containing composite meshes with three PP substrates were produced by integrating the NFM barrier compositing poly (lactic-co-glycolic acid) and polycaprolactone (PLGA/PCL) into each PP mesh. Tensile mechanical test results revealed that the PP component played a dominant role in the mechanical support, and this structure has not deteriorated in any case during the process. In vitro cell studies showed that the PP mesh with a higher density was significantly beneficial for cell proliferation within 3 days of seeding, while the one with lower density exhibited notable cell proliferation after a culture of 5 days. All the meshes had excellent biocompatibility. Moreover, an intraperitoneal implantation rabbit model was used to assess the anti-adhesion effects and tissue compatibility. The results revealed that the NFM barrier could be incorporated into the lightweight PP mesh to yield the composite mesh with superior anti-adhesion property and tissue compatibility.